Ideologi Puritan Dalam Tafsir Jawa Pesisir: Kajian Terhadap Penafsiran Misbah Mustofa - Pratama, Aunillah Reza (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2019)
The study examines the interpretation of the Coastal Javanese figure, Misbah Mustofa, who seems paradoxical to the traditionalist style of Islam which lies behind his socio-religious background. Misbah’s interpretation, indeed, shows the model of puritanical Islam. By using Hans Georg Gadamer’s hermeneutics, this article discusses Misbah’s interpretation of the QS. al-Baqarah [2]: 134, where he put his critics towards Javanese tradition, like tahlilan. The puritan style of Misbah’s interpretation is caused by several factors: First, the ideology of Coastal Javanese santri that makes Islamic sharia as a standard reference of religious teaching which tends to be more critical towards syncretic tradition of Javanese cults and rites. Second, Misbah’s pre-understanding of heresy and shirk. Third, the interpretation based on the general meaning, tends to be more textualist, and seems to ignore the virtue of socio-religious life of the community. The meaningful sense of Misbah’s interpretation is critical attitude towards religious teaching and proportionally locating permissive and conservative attitude in order to maintain the co-existance of religion and culture.